With Liberty and Some Justice for a Few: Thinking Theologically about Criminal Justice. (3rd June 2013) - Nelson, Derek R.
Abstract The current crisis in the American criminal justice system begs for theological response, and its sources need theological critique. The recent proposed statement of the ELCA draws attention to the needs of victims of crime and their families, and makes sensible recommendations for paths to greater justice. In doing so it is important to remember what forms of justice are possible under the jurisdiction of fallible, earthly institutions.